Critical factors of digital AgTech adoption on Australian farms: from digital to data divide. Issue 6 (26th April 2022) - Marshall, Amber; Turner, Krystle; Richards, Carol; Foth, Marcus; Dezuanni, Michael
ABSTRACT: As global agricultural production methods and supply chains have become more digitised, farmers around the world are adopting digital agricultural technologies (AgTech) such as drones, IoT, remote sensors, blockchain and satellite imagery to inform on-farm decision-making. Yet, on the backdrop of a persistent digital divide between rural and urban communities, many Australian farmers are not taking up digital AgTech. It has been argued that these farmers are being 'left behind' in an increasingly digital world, and this may impact their future success. Scholars of digital AgTech adoption typically take a siloed approach, positioning the individual or farm as the key unit of analysis, with fewer studies addressing structural conditions. This has provided a useful but incomplete understanding of the disparity between users and non-users. This paper builds upon emerging sociocultural approaches, which aim to address this gap, by using a novel 'communitive ecology' analytical approach to consider how adoption occurs through networks of actors. Based on an exploratory, qualitative study of a digital farming project on a cotton farm and its digital communicative ecology in South-East Queensland, Australia this study identifies technological, discursive, and social factors of digital AgTech adoption. Overall, an evolution from a digital divide to data divide, expressed in the interactions between farmers and stakeholders, and characterised by gaps between the generation and application of farm data, is observed.